Development of a Wordwall-Based Educational Game Test Instrument for Learning Outcomes in Qur’an Hadith at Madrasah Tsanawiyah - Anisah Fitri; Hamdanah; Abdullah Thahir; Muhammad Saleh; Marhani (Ta'dib, 2025)
This study aims to develop a test instrument based on the Wordwall educational game in order to make the learning process more engaging. The research was conducted using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), which consists of the following stages: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation. The Wordwall-based educational game test instrument was validated by media and content experts, followed by a feasibility trial involving 37 eighth-grade students of MTs DDI Wanio. The findings indicate that the developed Wordwall-based test instrument is valid, effective, and practical. Validity was confirmed by media expert validation at 88.6% and material expert validation at 81%. Effectiveness was demonstrated by improved learning outcomes, with 81.5% of trial participants achieving the minimum mastery criteria (KKM). Teacher activity observations showed 93.75%, while student responses reached 93%. Practicality was supported by the implementation rate and user response at 86.62%. The developed product can be accessed via https://wordwall.net/resource/94502507